A COMPREHENSIVE STUDY ON CYBER SECURITY THREATS AND PREVENTION MECHANISMS - Mariam Nayab,; Waqar Ahmad,; Abdullah Jahlil,; Jawaid Iqbal, (Spectrum of Engineering Sciences, 2025)
This article expresses emerging security threats and how we use different techniques to prevent them. As matter-of-fact previous research study shows just how to apply these security methods with different solutions but not provide future solutions as much as we need it in current time situation some of them explain universal security standards. This article contains future directions with emerging universal standards for cloud environment. The aim of writing this paper is to clarify the standards which help to protect from different threats like system data breaches, unauthorized access etc. cyber security is one of the leading process which help provide data and information protection and make sure to refrain from internet threats cyber bullying and online harassments. To control any type of internet security threats and vulnerabilities cyber security widely uses protraction measurements of every individual. Cyber securities reduce risk level based on different type’s situations like IOT weaknesses, IAM (Identify and access Management) and lie BYOD (Bring your own Device). In this study we purposing prevention techniques and also giving solution for prevention of common security threats.